Early mobile phone ownership: influencing the wellbeing of girls and boys in Ireland?. Issue 4 (1st October 2020) - Dempsey, Seraphim; Lyons, Seán; McCoy, Selina
ABSTRACT: Children live in a technology-mediated world, and most young people use a variety of technologies in their daily lives. However, despite intense public discourse, we have little empirical evidence on how technology use impacts on children's development across a number of psycho-social domains. Research that has been conducted tends to be largely small-scale or cross-sectional in nature and most often focused on (young) adults rather than children. Using longitudinal data on one-in-eight Irish children, we use econometric methods to test for associations between early mobile phone ownership and two measures of children's psycho-social development between 9 and 13 years of age. We examine the Piers Harris Self-Concept Scale, reported by children, and the Strengths and Difficulties (SDQ) score, completed by the primary caregiver. We find no generalised associations between early mobile phone ownership and psycho-social outcomes. However, there is evidence that associations differ by gender and across psycho-social sub-domains. We find no robust associations affecting boys, but girls who receive phones earlier fare less well in terms of their behavioural adjustment and academic self-concept scores at 13 years of age, all else being equal. Further research is needed to identify causal mechanisms and explore possible mediating effects of family/social context.